An Update to the iLab Shared Architecture for Mobile Device Support - Akinwale, Olawale Babatunde; Kehinde, Lawrence Olakunle (International Journal of Online and Biomedical Engineering (iJOE), 2017)
A number of remote laboratories and virtual laboratories have been created which support the mobile devices factor. The focus of a number of researchers at present is on the platforms which supports these online laboratories. This paper presents the solution we developed. The platform we developed is a modification of the iLab Shared Architecture (ISA) which was originally created by the Massachusetts Institute of Technology. It was expanded to include SMS services and WebSocket services. The goal was to ensure that it is able to support all mobile phones and tablets. Feature phones can perform experiments via SMS and tablets can use HTML5 based applications while personal computers can use the original ISA services.